2021
DOI: 10.3390/su132212581
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a Virtual Museum for the Dissemination of 3D Models of Historical Clothing

Abstract: Museums have been the main centers for the dissemination of cultural heritage throughout history. In recent years, they have been increasingly digitizing their content, so that it is now common for each museum to have free digital content available on the Web. This can be photographs of the works with detailed information or even objects created in three dimensions. It is also common to find virtual museums, which might be a representation of an existing museum that has been digitized or a museum created only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…To optimize the models for visualization, plane colors were used in simple clothing designs and complex designs were simplified by eliminating details and using image textures. Several characters were created, including knights, monks, nobles, and people from different social strata in the city, as seen in Figure 8 [59,65].…”
Section: The 3d Model Of the Citymentioning
confidence: 99%
“…To optimize the models for visualization, plane colors were used in simple clothing designs and complex designs were simplified by eliminating details and using image textures. Several characters were created, including knights, monks, nobles, and people from different social strata in the city, as seen in Figure 8 [59,65].…”
Section: The 3d Model Of the Citymentioning
confidence: 99%
“…Other research has focused on evaluating the performance of users' avatars, which increasingly become a critical element in the development of commercial offers by involving analysis of the user's projected behavior, i.e., the person's consumption preferences will not necessarily coincide with those of their avatar [53]. An important experience in the literature is the virtual services that have been rising due to the present pandemic such as virtual museum visits [54] and virtual tourism [55]. Moreover, it was reported that religious activities impact the metaverse [56].…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the continuous improvement of 3D virtual simulation technology, it is widely used in various fields, such as interactive design of clothing (Volino et al, 2005 ; Wang et al, 2021 ; Xin et al, 2021 ),interactive virtual real-time fitting of users (Jiang et al, 2019 ),Evaluation of clothing comfort (Haixia & Yongrong, 2019 ; Meng et al, 2010 ),proposal of efficient methods for 3D clothing design (Zhang et al, 2018 ), improvement of realism of clothing virtual simulation (Cheng et al, 2020 ; Zhu et al, 2021 ). Virtual simulation technology application on a 3D virtual costume museum (Lei et al, 2017 ; Martin et al, 2016 ; Meier et al, 2021 ) etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Italian fashion house Valentino ran an online virtual museum called the Valentino Garavani Virtual Museum in 2011. Meier et al ( 2021 ) created a completely virtual museum of sixteenth century Spanish costumes in 2021, with a 360° view of each garment. 3D virtual Brooklyn Museum, which showcases some of the costumes from the two Netflix shows "The Queen's Gambit" and "The Crown", allows a 360° view of the costumes, click on a costume to see some of the details of the costume in picture form.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation